RESPON BAWANG MERAH (Allium ascalonicum L) TERHADAP ZAT PENGATUR TUMBUH DAN UNSUR HARA - Mokhamad Irfan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2013)
Test of effect of plant regulator and leaf fertilizer to shallots have conducted in Agriculture and Animal Sciences Faculty, The State Islamic University of Sultan Syarif Kasim Riau. The experimental design used A Completely Randomized Design by one factor, 3 replications, and 7 treatments. The treatments namely were F0 = As controlled, F1= Multi micro fertilizer, F2 = Macro and micro fertilizer, F3 = Macro and micro fertilizer plus vitamins, F4 = Vitamins, minerals and proteins, F5 = Plant regulator with single strength and F6 = Plant regulator with triple strength. Parameters of research were tuber diameter, long of tuber, hight of plant, number of fresh leaf, number of tuber per clump, weight of plant per clump and rates of tuber weight. The results showed that by given minor element (macro-micro), vitamins, protein and Plant Regulator in dosage normal or triple on agriculture system of shallot in optimal condition could not increase the tuber diameter, length of tuber, height of plant, amount of leaf, amount of tuber per clump and weight of plant.